Digital marketing evolution: Understanding the role of AI and Big Data in shaping marketing strategies - Rahman, Shandikha Arya Yudha; Rahayu, Agus; Hendrayati, Heny (Goodwood Publishing, 2025)
Purpose: This study explores the evolution of digital marketing and the role of Artificial Intelligence (AI) and Big Data in enhancing marketing effectiveness. As market complexity and consumer needs continue to evolve, companies must adopt new technologies to optimize their strategies. Methodology/approach: This research employs a comprehensive literature review, analyzing journal articles, industry reports, and case studies related to AI and Big Data in digital marketing. The process involves selecting and evaluating relevant sources to gain in-depth insights into their impact on marketing strategies. Results/findings: The study finds a positive correlation between AI implementation in digital marketing and improved campaign effectiveness. Companies leveraging AI report increased consumer engagement and higher sales conversions. Moreover, integrating Big Data and AI enhances customer satisfaction and loyalty. Firms adopting these technologies demonstrate greater adaptability to market dynamics and evolving consumer preferences. Conclusion: The study concludes that AI and Big Data play a crucial role in shaping digital marketing strategies by enabling personalization, predictive analytics, and data-driven decisions. Although challenges such as privacy concerns and algorithmic bias remain, their benefits far outweigh the risks, offering firms a sustainable competitive advantage. Limitations: The study is limited to existing literature, which may introduce selection bias. Additionally, the absence of empirical analysis restricts deeper insights into AI and Big Data applications in marketing. Contribution: This research provides a deeper understanding of AI and Big Data’s impact on digital marketing strategies. The findings assist marketers in developing more effective and adaptive strategies.